Recent Progress In Biotechnological Interventions In Piper Species: A Review (Applied Biological Research, 2016)
Medicinal plants have tremendous potential for the development of new  drugs molecule effective against various diseases. Genus Piper is the largest  genus in family Piperaceae and indigenous to India with one of the most  widely used spice in the world. Biotechnological innovations in Piper species  have lead to the development of plant-derived molecules which exhibit a  promising effect in therapeutics. The present paper reviews the genetic  diversity analysis of major Piper species through DNA markers, to establish  in vitro protocol for mass multiplication of elite clone of different species,  phytochemical compounds extracted in various solvent systems in Piper  species and comparative analysis of active compounds associated with Piper  species through HPTLC analysis as well as testing their antimicrobial  activities. The activity has been tested against bacteria like E. coli,  Micrococcus luteus, Streptomyces epidermidis, etc. and fungi like Aspergillus  niger, A. flavus and Rhizoctonia solani using agar well diffusion method.  The review also highlights the use of in vitro strategy in genetic  manipulation of transgenic traits using specific promoters to accomplish  high tissue specific protein production and overcome biotic stresses.
Keywords: Antimicrobial properties; genetic diversity; Piper species; secondary metabolites; genetic engineering